Holiness and taboo in the Zion Christian Church - S Moripe (Acta Theologica, 1998)
Taboo is a Polynesian word, which literally means something marked out as forbidden. The concept of taboo is closely linked with the concept mania. Mana is a mysterious kind of supernatural power, a potential energy which people believe to be in and behing all men/women and things. This mana makes a thing, a human being or an animal that which they are. Everything can have mana, but if a thing is big and strong, or when a man/woman has exceptional talents and when something or someone is powerful or dangerous, then it is believed that it or he/she has much mana. Mana is like an electric charge.